Design of Digital Scoring for Pencac Silat IPSI Branch in Padang City - Ashabul Khairi; Gufron Gufron; Ali Mardius; M. Ichsan Fajri Saib (Budapest International Research and Critics University, 2022)
The development of Information and Communication Technology affects every aspect of human life, including in the field of Pencak Silat. In Pencak Silat matches, the scoring system has started to usedigital scoringand has begun to gradually leave the assessment blanks in the form of paper. In West Sumatra, Pencak Silat is a traditional martial art that has developed in all districts, as can be seen from the enthusiasm of participants in participating in Pencak Silat championships which are often held by the Indonesian Pencak Silat Association (IPSI) of the West Sumatra Provincial Government. However, the assessment tool does not yet use digital scoring. The purpose of this study is to design and produce a digital scoring application that meets the assessment aspects in the TGR (Single, Double Team) pencak silat competition category or the sparring category by prioritizing value transparency to improve the quality of Pencak Silat matches in West Sumatra. The digital scoring was developed with PHP which is used as a server-side scripting in web development that allows web applications to be dynamically created. The Digital Scoring which is designed to refer to the match rules of the 2016 IPSI XVI National Conference results is not only limited to hitting and kicking techniques but there are also other techniques such as slamming, pulling, elbowing, kneeling and so on which are declared as legitimate and valuable attacks. The system development method used in this research is the waterfall. namely a sequential software development method, where the process flows from top to bottom like awaterfall, passing through the phases of planning, modeling, implementation, testing and maintenance.